Part 1: Mechanistic insights into the photochemistry of tetrazolethiones Part 2: Synthesis of phenanthridine-fused quinazoliniminium and computational investigation of their optoelectronic properties - Alawode, Olajide E. (Kansas State University, 2012)
Research in our laboratory has focused on designing photoactivated DNA cleaving agents based on tetrazolethione scaffolds. The key step in the activation of these involves conversion of tetrazolethione moiety to carbodiimides upon irradiation. However, the mechanism of this reaction was not previously reported. Therefore, we undertook a study to elucidate the mechanism of photodecomposition of tetrazolethione as to identify reactive intermediates involved, that may interfere or aid with the activity of our synthesized DNA cleaving agents under physiological conditions. In Part 1 of this dissertation, we present mechanistic studies on this photodecomposition. Our results indicate the clean photoconversion of tetrazolethiones I to their respective carbodiimides IV via the expulsion of sulfur and dinitrogen. Photoirradiation in the presence of trapping agent (e.g. 1,4-cyclohexadiene) resulted into the formation of their corresponding thioureas. Thus, providing strong evidence for the intermediacy of a 1,3-biradical III, which is believed to be in its triplet spin multiplicity. Further investigations (triplet sensitization and quenching experiments) to determine the precursor of the biradical argued against the involvement of a triplet excited state (T[subscript]1). We believe that the mechanistic pathway that leads to the formation of a 1,3-triplet biradical III is a diradicaloid species II-II" generated directly from the singlet excited state of tetrazolethiones (S[subscript]1) after the expulsion of dinitrogen. Once formed, this diradicaloid species could be envisioned to undergo intersystem crossing to generate the 1,3 triplet biradical III which then undergoes desulfurization to form carbodiimides IV (Chapter 2). Bridgehead-nitrogen containing fused heterocycles are regarded as “privileged structure” in biology and have found widespread applications in pharmaceutical industry. These heterocycles have also been evaluated in electroluminescent devices and organic dyes. Part II of the dissertation present new, concise and low cost strategies to a unique class of bridgehead nitrogen-containing fused heterocyclic scaffolds which involves two sequential intramolecular cyclizations from heteroenyne-allenes in the presence of Lewis acids such as SnCl[subscript]4 and BF[subscript]3.OEt[subscript]2, and trace water. The starting heteroenyne-allenes VI can be prepared from commercially available substrates V in 4 – 5 steps following standard protocols (Chapter 3). Furthermore, we employed density functional theory to gain insights into the optoelectronic properties of select derivatives of phenanthridine-fused quinazoliniminiums (PNQs) VII and their free base in order to evaluate their scope in OLED technology. Our results show that the energies of the Highest Occupied Molecular Orbital (HOMO), Lowest Unoccupied Molecular Orbital (LUMO), the HOMO-LUMO energy gaps, the ionization potentials, electron affinities and the reorganization energies can be finely tuned by varying the substituents on these chromophores. In addition, we found that the introduction of an electron donating group (NMe[subscript]2) on the PNQs and their free base increases the energies of the HOMOs and decreases the ionization potentials, relative to its unsubstituted derivative, whereas substitution by an electron withdrawing group (NO[subscript]2) decreases the energies of the LUMOs and increases the electron affinities which in turn suggests an improvement in their hole and electron creating abilities, respectively (Chapter 4).
Keywords: Photodecomposition Mechanism; Tetrazolethione; Quinazoliniminiums salts; Phenanthridine-fused quinazoliniminiums; N-fused heterocycles; Optoelectronic PNQs; Chemistry (0485); Organic Chemistry (0490); Physical Chemistry (0494)